El “iusnaturalismo” de Thomas Hobbes - Hernández, Javier Felipe (2023)
One of the most controversial issues surrounding the study of Thomas Hobbes has be en his classification as a proponent of either natural law theory or legal positivism. Some authors find in Hobbes the roots of modern legal positivism, while others think he is one of the main figures in the formation of the modern theory of natural right s. In this article, the author examines the way in which Hobbes understood and used the concepts of ius naturale and l ex naturalis , and shows the fundamental changes he introduced to these concepts’ previous uses and meanings. Finally, this paper will show that the alleged paradox in which Hobbes fell by using natural law theory to reach a positive law conclusion responds to the fact that he introduced the idea of ius naturale as an unlimited faculty and that he found human reason to be essentially utilitar ian.